The Investigation of Glass Spheres Containing Elastomer Based Materials for Tunable Device Applications - Senturk, E.; Okutan, M.; Demirer, A.; Akcakale, N. (WALTER DE GRUYTER GMBH, 2014)
In this work, dielectric and tunability properties of glass spheres containing elastomer based materials have been investigated with dielectric spectroscopy as a function of frequency, composition and DC bias field. Real and imaginary part of dielectric constant and dielectric loss values of the gs1 (glass spheres), gs2, and gs3 were investigated in the frequency range of 100 to 40 x 10(6) Hz. Dielectric tunabilities of 69%, 87% and 33% were measured on gs1, gs2, and gs3 at 10 kHz and at room temperature. The degrees of anharmonic contributions to the polarization are very high for gs2 and gs3 as 4.53 x 10(-8) and 1.77 x 10(-8) (mm/kV)(2). Also, dielectric constant, FOM (%) and absorption coefficient alpha values were calculated at 10 x 10(3) Hz and 20 x 10(3) V/mm depending for different glass spheres.
Keywords: tunability; dielectric constant; loss factor; DC bias; polarization; BA0.5SR0.5TIO3 THIN-FILMS; DIELECTRIC-PROPERTIES; COMPOSITE CERAMICS; Materials Science